Predictive accuracy of political stock markets: Empirical evidence from an European perspective - Michael Berlemann; Carsten Schmidt (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2001)
In a meta study of 25 political stock markets conducted in Germany in the last decade we analyze their predictive success. Although the predictions of political stock markets are highly correlated with the corresponding polls, the markets are able to aggregate additional information. One explanatory variable for variations in predictive success of the German stock markets relative to the polls is market efficiency. Even though the overall predictions of the political stock markets are quite reliable on the aggregate level we find systematic prediction errors on the contract level that can be attributed to the vote share size and to individual trader biases.
Keywords: C93; D82; G1; 330; political stock markets; forecasting; market efficiency; proportional representation; Wahlverhalten; Prognoseverfahren; Börse; Effizienzmarktthese; Deutschland